Bypassing the emergency room reduces delays and mortality in ST elevation myocardial infarction: the USIC 2000 registry. Issue 10 (16th August 2006) - Steg, P G; Cambou, J-P; Goldstein, P; Durand, E; Sauval, P; Kadri, Z; Blanchard, D; Lablanche, J-M; Guéret, P; Cottin, Y; Juliard, J-M; Hanania, G; et al.
Abstract : Objective: To study the impact on outcomes of direct admission versus emergency room (ER) admission in patients with ST-segment elevation myocardial infarction (STEMI) Design: Nationwide observational registry of STEMI patients Setting: 369 intensive care units in France. Interventions: Patients were categorised on the basis of the initial management pathway (direct transfer to the coronary care unit or catheterisation laboratory versus transfer via the ER). Main outcome measures: Delays between symptom onset, admission and reperfusion therapy. Mortality at five days and one year. Results: Of 1204 patients enrolled, 66.9% were admitted direct and 33.1% via the ER. Bypassing the ER was associated with more frequent use of reperfusion (61.7% v 53.1%; p  =  0.001) and shorter delays between symptom onset and admission (244 (interquartile range 158) v 292 (172) min; p < 0.001), thrombolysis (204 (150) v 258 (240) min; p < 0.01), hospital thrombolysis (228 (156) v 256 (227) min, p  =  0.22), and primary percutaneous coronary intervention (294 (246) v 402 (312) min; p < 0.005). Five day mortality rates were lower in patients who bypassed the ER (4.9% v 8.6%; p  =  0.01), regardless of the use and type of reperfusion therapy. After adjusting for the simplified Thrombolysis in Myocardial Infarction (TIMI) risk score, admission via the ER was an independent predictor of five day mortality (odds ratio 1.67, 95% confidence interval 1.01 to 2.75). Conclusions: In this observational analysis, bypassing the ER was associated with more frequent and earlier use of reperfusion therapy, and with an apparent survival benefit compared with admission via the ER.